2020
DOI: 10.1038/s41598-020-79097-1
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of disease progression in patients with COVID-19 by artificial intelligence assisted lesion quantification

Abstract: To investigate the value of artificial intelligence (AI) assisted quantification on initial chest CT for prediction of disease progression and clinical outcome in patients with coronavirus disease 2019 (COVID-19). Patients with confirmed COVID-19 infection and initially of non-severe type were retrospectively included. The initial CT scan on admission was used for imaging analysis. The presence of ground glass opacity (GGO), consolidation and other findings were visually evaluated. CT severity score was calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…In one study GGO with consolidation was more frequently revealed in progress to severe group whereas pure GGO was more likely to be found in non-severe group [18].…”
Section: Discussionmentioning
confidence: 91%
“…In one study GGO with consolidation was more frequently revealed in progress to severe group whereas pure GGO was more likely to be found in non-severe group [18].…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, this distinction is important and may have immediate therapeutic repercussions, and imaging may help (26,27). There are also other studies showing that adequate characterization of the opacities and a pattern categorization on CT can be important, highlighting the presence and extent of consolidations as a potential prognostic feature in the imaging evaluation of the disease (28)(29)(30). At last, a very recent document (31) from the European Society of Thoracic Imaging (ESTI) and the European Society of Radiology (ESR) discusses the role of imaging in the longterm follow-up of COVID-19 patients.…”
Section: B C Amentioning
confidence: 99%
“…A summary of the aforementioned examples and their evaluation matrices are listed in Table 1 . Furthermore, lung lesion characterized by chest computed tomography (CT) scans were also proposed to predict disease progression ( Liu et al, 2020 , Li et al, 2020 , Wang et al, 2020b). An algorithm combining the imaging, clinical and biological attributes has been further constructed based on deep convolutional neural networks to generate a holistic forecast model, which has an area under curve (AUC) of 0.86 and 0.76 for predicting short-term and long-term mortality, respectively ( Chassagnon et al, 2021 ).…”
Section: Disease Predictionmentioning
confidence: 99%